PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL PEMEDIASI PADA BADAN PERTANAHAN NASIONAL (BPN) TANGGAMUS, LAMPUNG - Ristian Lilis; Tasya Monica; Rudi Stiawan; Vicky F Sanjaya (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
The purpose of this study was to examine the effect of leadership style on employee performance and to examine organizational culture as the influence between leadership style and employee performance. This study used a descriptive quantitative method by taking a sample of 55 employees who were collected using a questionnaire with a 5-point Likert scale. The data analysis used was a structural equation model with the partial least square (PLS-SEM) method using the smartPLS application. The results showed that the Leadership Style was able to improve employee performance directly or indirectly, namely through enhancing organizational culture and having an impact on improving employee performance.